2020
DOI: 10.1186/s13071-020-04260-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protective peptides of Fasciola hepatica-derived cathepsin L1 (FhCL1) in vaccinated sheep by a linear B-cell epitope mapping approach

Abstract: Background Fasciolosis is one of the most important parasitic diseases of livestock. The need for better control strategies gave rise to the identification of various vaccine candidates. The recombinant form of a member of the cysteine protease family, cathepsin L1 of Fasciola hepatica (FhCL1) has been a vaccine target for the past few decades since it has been shown to behave as an immunodominant antigen. However, when FhCL1 was used as vaccine, it has been observed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
(80 reference statements)
2
6
0
Order By: Relevance
“…These results observed in group 1 agree with previous studies where high levels of antibodies were related with protection against Fasciola hepatica in ruminants [16,21,37,44]. Furthermore, it was reported in sheep immunised with the same vaccine formulation of group 1, the recognition of different CL1 overlapping peptides from those observed in group 2 and 3, supporting the hypothesis of induction of immune protection with the combination of Montanide and cocktail antigen [24]. Similar results to those reported in sheep were also observed in cattle [49].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results observed in group 1 agree with previous studies where high levels of antibodies were related with protection against Fasciola hepatica in ruminants [16,21,37,44]. Furthermore, it was reported in sheep immunised with the same vaccine formulation of group 1, the recognition of different CL1 overlapping peptides from those observed in group 2 and 3, supporting the hypothesis of induction of immune protection with the combination of Montanide and cocktail antigen [24]. Similar results to those reported in sheep were also observed in cattle [49].…”
Section: Discussionsupporting
confidence: 91%
“…These divergences between the level of protection reported and our results might be attributed to major differences in the vaccine formulation used, which may have led to the development of contrasting results in terms of vaccine efficacy. For instance, we recently reported significant B cell-based immune response differences in sheep when the same F. hepatica antigens were administered with different adjuvants, which resulted in diverse level of protection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping the four epitopes recognised by experimentally infected animals onto a 3D model of the CL1 protein showed that these eptitopes are located on the surface of the protein and away from the active site, indicating they are unlikely to prevent functional activity of the enzyme. Other studies have identified similar epitopes on CL1, using computational software ( Cornelissen et al, 1999 ), phage display of random 12-mers peptides using rabbit anti- CL1/CL2 sera ( Villa-Mancera et al, 2008 , 2011 ; Villa-Mancera and Mendez-Mendoza, 2012 ; Villa-Mancera et al, 2014 ), or using peptide ELISAs and sera from experimentally infected cattle and sheep as part of vaccine trials ( Garza-Cuartero et al, 2018 ; Buffoni et al, 2020 ). The epitopes identified in our study were in similar regions ( Villa-Mancera et al, 2008 , 2011 ; Villa-Mancera and Mendez-Mendoza, 2012 ; Villa-Mancera et al, 2014 ) but differed to epitopes identified in other studies ( Garza-Cuartero et al, 2018 ; Buffoni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may also represent a parasite strategy to avoid a host immune response that could prevent peptidase activation. Indeed, recently Buffoni et al [ 38 ] have shown that immune responses in animals protected by vaccination with FhCL1 were directed to peptides that span the junction between propeptide and the mature domain of the peptidase.…”
Section: Discussionmentioning
confidence: 99%